1986
DOI: 10.1017/s0021859600087220
|View full text |Cite
|
Sign up to set email alerts
|

Growth, nitrogen uptake and partitioning within the potato (Solatium tuberosum L.) crop, in relation to nitrogen application

Abstract: The effects of nitrogen applications, ranging from 0 to 25 g N/m a , on the nitrogen uptake and growth of the potato crop was studied in an experiment in both 1983 and 1984. Nitrogen uptake was substantially increased by fertilizer application. At high rates of nitrogen application, the crops took up more than was needed to satisfy their immediate requirements for growth. Initially, this extra nitrogen appeared predominantly in the form of soluble protein in the leaves and nitrate in the stem, with reduced-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
40
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 24 publications
14
40
0
Order By: Relevance
“…Since HI(N) at 300 N was lower in these crops than that at 100 N, it is considered that there was some delay in the utilization of nitrogen or in the nitrogen distribution in these crops when large amount of nitrogen were absorbed. It has been reported that nitrogen compounds with low molecular weight, such as FAA and nitrate, accumulated in plants as a result of the excess of nitrogen application (Millard 1986;Matsumaru et al 1987;Millard and Catt 1988). In the stems, the proportion of FAA-N to total-N in rice and soybean, that of nitrate-N in potato and both in wheat and maize increased with the increase of the level of nitrogen application (Table 7).…”
Section: Discussionmentioning
confidence: 95%
“…Since HI(N) at 300 N was lower in these crops than that at 100 N, it is considered that there was some delay in the utilization of nitrogen or in the nitrogen distribution in these crops when large amount of nitrogen were absorbed. It has been reported that nitrogen compounds with low molecular weight, such as FAA and nitrate, accumulated in plants as a result of the excess of nitrogen application (Millard 1986;Matsumaru et al 1987;Millard and Catt 1988). In the stems, the proportion of FAA-N to total-N in rice and soybean, that of nitrate-N in potato and both in wheat and maize increased with the increase of the level of nitrogen application (Table 7).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, oversupply of nitrogen during early growth stages causes excessive growth of the foliage, resulting in too large a canopy for optimal yield development (Krauss 1978, Kuisma 1995. Nitrogen itself has little effect on the amount of dry matter produced per unit of intercepted solar radiation (Millard and Marshall 1986). The slower canopy development of crops under low nitrogen supply can be explained mainly through reduced effi ciency of fertilizer use and decline in supply of nitrogen to the crops under cool weather conditions.…”
Section: Mustonen L Yield Formation Of Early Potatoes During a Shormentioning
confidence: 99%
“…In early potato production, when tubers are harvested at low yield, low dry matter content creates a soggy texture and decreases potato quality. Under conditions of increased nitrogen supply the potato crop has the ability to take up nitrogen in excess to that required for growth and store it as nitrate in the vacuoles (Millard and Marshall 1986). Potato tubers normally have low nitrate content, not exceeding 300 mg kg -1 in fresh matter (Blom-Zandstra 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the nitrogen concentration of leaves remains high due to the application of a large amount of nitrogen, the photosynthetic rate is likely to remain high during growth. However it has been reported (Dyson and Watson 1971;Karauss 1978;Millard and Marshall 1986;Osaki et al 1992), that a large amount of nitrogen applied as basal fertilizer stimulated only the shoot growth, and did not affect appreciably the tuber yield. It was, thus, considered that the canopy structure and physiological conditions deteriorated by heavy nitrogen application (Osaki et al 1991).…”
mentioning
confidence: 92%